Da produção à preservação informacional: desafios e oportunidades - Nelson Vaquinhas, Marisa Caixas, Helena Vinagre (dir.) (Publicações do Cidehus, 2017)
This book focus in the study of past information systems, current information management and digital preservation. It results from a set of text sources, whose approaches reflect the challenges and opportunities in the world of information, treated by specialists dealing with it on a professional and academic level. The objective of this collection of text sources is to be a motto to new contributions to the archival field, potentiating experiences in the work context and new studies in the a...